Using Marital Status and Continuous Marital Satisfaction Ratings to Predict Depressive Symptoms in Married and Unmarried Women With Systemic Sclerosis: A Canadian Scleroderma Research Group Study. Issue 8 (August 2016) - Levis, Brooke; Rice, Danielle B.; Kwakkenbos, Linda; Steele, Russell J.; Hagedoorn, Mariët; Hudson, Marie; Baron, Murray; Thombs, Brett D.; ,
Abstract : Objective: Married persons have, on average, better mental health than nonmarried persons. Among married persons, marital satisfaction is associated with better mental health. Studies on mental health in married and nonmarried persons that consider marital satisfaction have categorized patients as satisfied versus unsatisfied, which reduces statistical power and does not generate clinically useful information on mental health across the satisfaction spectrum. Our objective was to demonstrate a novel regression approach to evaluate mental health in women with systemic sclerosis (SSc), comparing married and unmarried women, accounting for continuously measured marital satisfaction. Methods: Depressive symptoms were assessed using the Center for Epidemiologic Studies Depression Scale (CES‐D) and marital satisfaction with the Dyadic Adjustment Scale‐7. A single multiple linear regression model was used to predict CES‐D scores from marital status and, among married women, continuously measured marital satisfaction, controlling for demographic and clinical characteristics. Results: Of 725 women, 494 (68%) were married or living as married. On average, married women had mean CES‐D scores that were 2.0 points (0.19 SDs) lower than unmarried women ( P = 0.013). Among married women, a 1.0 SD increase in marital satisfaction was associated with a 2.2 point (0.21 SDs) decrease in CES‐D scores ( P < 0.001). Married women whose marital satisfaction scores were below the 19th percentile had greater predicted depressive symptoms than unmarried women. Married women's predicted CES‐D scores ranged from 6.7 points lower to 6.9 points higher than those of unmarried women, depending on marital satisfaction. Conclusion: Comparisons of mental health in married and unmarried patients with rheumatic diseases should include continuously measured marital satisfaction.